Psychopathic traits and reinforcement learning under acute stress - Carvalheiro, Joana (2022)
Objective Individuals with high levels of psychopathic traits are often characterized by aberrant reinforcement learning. This type of learning, which implicates making choices that maximize rewards and minimize punishments, may be affected by acute stress. However, how acute stress affects reinforcement learning in individuals with different levels of psychopathic traits is not well-understood. Here, we investigated whether and how individual differences in psychopathic traits modulated the impact of acute stress on reward and punishment learning. Method Sixty-two male participants from a university sample completed the Self-Report Psychopathy-Short Form scale and performed a reinforcement-learning task involving monetary gains and losses whilst under acute stress and control conditions. Results Individual differences in psychopathic traits modulated the impact of acute stress on behavioral performance toward obtaining gains, but not toward avoiding losses. As levels of psychopathic traits increased, the impairing effect of acute stress on reward learning decreased. Specifically, acute stress impaired performance toward seeking gains to a larger extent in individuals with lower levels of psychopathic traits than in individuals with higher levels of these traits. Conclusions Our study indicates that psychopathic traits modulate the impact of acute stress on reward learning.